2018
DOI: 10.3389/fendo.2018.00469
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Agonists for Pituitary Adenomas

Abstract: Dopamine agonists (DA) are well established as first-line therapy for prolactinomas. These tumors express high levels of dopamine 2 receptors (D2R), leading to the strong efficacy of DA in reducing tumor size and hormonal secretion. Other pituitary tumor subtypes express D2R to varying degrees, leading to an extensive body of research into potential off-label use of DA in non-prolactinoma pituitary tumors. Preclinical models of Cushing's disease, acromegaly, and nonfunctioning pituitary tumors (NFPT) demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 96 publications
(111 reference statements)
2
21
0
2
Order By: Relevance
“…70%) was also reported in the other studies [27,28]. These results corroborate with the reported efficacy of the postoperative treatment of CNFPAs with dopamine agonists [27,29,30]. Our observation that the expression of RD2 concerns equally PRL-positive as PRL-negative CNFPAs suggests that the latter are also good candidates for the treatment with dopamine agonists.…”
Section: Discussionsupporting
confidence: 91%
“…70%) was also reported in the other studies [27,28]. These results corroborate with the reported efficacy of the postoperative treatment of CNFPAs with dopamine agonists [27,29,30]. Our observation that the expression of RD2 concerns equally PRL-positive as PRL-negative CNFPAs suggests that the latter are also good candidates for the treatment with dopamine agonists.…”
Section: Discussionsupporting
confidence: 91%
“…Good response to DA was observed more in males as all our patients (100%) that totally cured and had no residual mass during follow up were males and 20% of patients that had tumor reduction were males. Cooper and Greenman [13] reported the largest series of NFPT patients who were treated with DA. In one of the groups that they studied, fifty five patients received preventive DA treatment and twenty four patients received treatment after tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Ferriere et al [224], who conducted a multicenter retrospective study of 53 CD patients, showed that about 20–25% of CD patients showed good response to cabergoline therapy, allowing the long-term control of hypercortisolism at relatively low dosages (1.5 mg/week) and with acceptable tolerability. In those responders, metabolic symptoms associated with CD resolved and tumor size decreased or remained stable [225]. However, even in patients who responded initially, subsequent follow-up studies showed no sustained control of hypercortisolism (therapeutic escape), which could result in lower long-term efficacy [223,224].…”
Section: Treatmentmentioning
confidence: 99%